2017
DOI: 10.6007/ijarems/v6-i1/2570
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Commitment of the Employees of the Ports Security Affairs of the State of Kuwait: The Impact of Human Recourses Management Practices

Abstract: The aim of the study was to explore the impact of human resource management practices on organizational commitment of the Ports Security Affairs of the State of Kuwait. The HRM practices applied in this study were human resource planning, recruitment and selection, rewards and incentives, training and development, and performance appraisal. Organizational commitment dimensions used in this study were affective commitment, normative commitment and continuance commitment. All managerial employees working in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The organisational commitment is not affected by job satisfaction [7] but it is more about employees' feeling towards the organisation [14] and the capability of organisation to satisfy the employees [15]. This feeling leads to positive behaviours among the employees [16]. However, the organisational commitment has greater impacts on job loyalty and could be achieved through three dimensions of affective, continuance and normative commitments [17].…”
Section: Past Researchesmentioning
confidence: 99%
“…The organisational commitment is not affected by job satisfaction [7] but it is more about employees' feeling towards the organisation [14] and the capability of organisation to satisfy the employees [15]. This feeling leads to positive behaviours among the employees [16]. However, the organisational commitment has greater impacts on job loyalty and could be achieved through three dimensions of affective, continuance and normative commitments [17].…”
Section: Past Researchesmentioning
confidence: 99%
“…Job performance is critical factor in determining the organizational performance (Al-Hawary & Al-Kumait, 2017). Previous literature has shown that employees who are not properly matched to job characteristics have a low job performance (Hawary & Alajmi, 2017). Matching the person with the job in the organization can be a real indicator of job performance, because it has been shown that individuals who match the job more have higher functional outcomes (Al-Hawary & Al-Namlan, 2018;Al-Hawary & Nusair, 2017;Edwards, 1991).…”
Section: Introductionmentioning
confidence: 99%